2015
DOI: 10.1016/j.ajpath.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Cancer–Derived Immunosuppressive Plasmacytoid Dendritic Cells Release IL-1α in an AIM2 Inflammasome-Dependent Manner

Abstract: Plasmacytoid dendritic cells (pDCs) highly populate lung tumor masses and are strictly correlated to bad prognosis, yet their role in lung cancer is controversial. To understand their role in lung cancer, we isolated pDCs from human samples of lung obtained from non-small cell lung cancer patients undergoing thoracic surgery. Tumor masses presented a higher percentage of pDCs than healthy tissues; pDCs were in the immunosuppressive phenotype, as determined by higher levels of CD33 and PD-L1. Despite higher HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 34 publications
(64 reference statements)
3
85
0
Order By: Relevance
“…Previous studies have shown that AIM2 was differently expressed and functioned as both a tumor suppressor and oncogene in human cancers. AIM2 was overexpressed in nonsmall cell lung cancer and facilitated cell proliferation (Kong et al ., 2015; Sorrentino et al ., 2015). AIM2 restoration in colorectal cancer cells induced the expression of invasion‐associated genes such as VIM and MCAM (Patsos et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that AIM2 was differently expressed and functioned as both a tumor suppressor and oncogene in human cancers. AIM2 was overexpressed in nonsmall cell lung cancer and facilitated cell proliferation (Kong et al ., 2015; Sorrentino et al ., 2015). AIM2 restoration in colorectal cancer cells induced the expression of invasion‐associated genes such as VIM and MCAM (Patsos et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that AIM2–dependent release of alarmins promotes tumorigenesis . Increased production of IL‐1α from immunosuppressive tumor‐associated plasmacytoid dendritic cells (pDCs) in lung cancer depends on the AIM2 inflammasome . Disrupted mitochondrial iron metabolism in the absence of the mitophagy proteins PINK1 and PARK2 induces AIM2‐dependent high mobility group box 1 release in pancreatic ductal adenocarcinoma, promoting the upregulation of immune checkpoint protein programmed cell death ligand 1 .…”
Section: Role Of Aim2 In Sterile Inflammatory Diseasesmentioning
confidence: 99%
“…For instance, in ovarian cancer, pDCs modulate neo-angiogenesis via TNF-α and IL-8 production upon CD40L activation [139]. Recently, it has been demonstrated that TA-pDCs produce the pro-angiogenic and pro-invasive cytokine IL-1α in an AIM2-dependent manner, and promote tumor cell proliferation and angiogenesis in NSCLC [182]. Finally, the secretion of GrB could be an additional tolerogenic mechanism of pDCs [97,99].…”
Section: The Dual Role Of Pdcs In Human Cancermentioning
confidence: 99%